Changing Scotland evidence from the British Household Panel Survey - Ermisch, John 1947-; Wright, Robert 1958- (Policy Press, University of Bristol, 2005)
Changing Scotland uses longitudinal data from the British Household Panel Survey (BHPS) to improve our knowledge and understanding of the impact of devolution on the lives of people in Scotland. It is the first time that BHPS data has been used in this way
Title from publisher's bibliographic system (viewed on 20 Jan 2022)
Keywords: Geschichte 1990-2000; Households / Scotland; Household surveys / Scotland; Soziale Situation; Wirtschaftliche Lage; Haushalt; Scotland / Social conditions / 20th century; Scotland / Economic conditions / 20th century; Scotland / Politics and government / 20th century; Schottland; Aufsatzsammlung